New heterogeneous catalyst for the esterification of fatty acid produced by surface aromatization/sulfonation of oilseed cake. (15th June 2015) - Santos, Eleonice Moreira; Teixeira, Ana Paula de Carvalho; da Silva, Flávia Gontijo; Cibaka, Thérèse Ebambi; Araújo, Maria Helena; Oliveira, Willian Xerxes Coelho; Medeiros, Felipe; Brasil, Alex Nogueira; de Oliveira, Leandro Soares; Lago, Rochel Montero
Highlights: Simple sulfonation of biodiesel waste cake in mild conditions produces a new and active heterogeneous acid catalyst. The catalytic activity is comparable to H2 SO4 and the catalyst can be reused several times. The catalyst combines a carbon-sulfonic acid surface with a very hydrophilic cellulose surface responsible for water removal. Abstract: In this work, an efficient heterogeneous acid catalyst for the esterification of oleic acid was prepared directly from oilseed cake by a simple sulfonation with concentrated H2 SO4 . Characterization by SEM/EDS, IR, Raman, TG, TG/MS, potentiometric titration showed that treatment with H2 SO4 for 1, 2 and 4 h at 120 °C partially dehydrates the cake to form a carbon/cellulose composite which is sulfonated to produce strong SO3 H acidic sites. These surface sites were active for the esterification of oleic acid with yields ca. 84%, 88% and 94% in the presence of 5, 10 and 20 wt% catalyst, respectively. These results are comparable to 98% yield obtained with 1 wt% H2SO4 and higher than 75% observed for a high surface area (880 m 2  g −1 ) sulfonated activated carbon with similar number of SO3H active groups. These results are discussed in terms of two effects: (i) the number of sulfonic surface acidic groups and (ii) the presence of a hydrophilic cellulosic fraction in the catalyst that adsorbs/traps water formed in the reaction shifting the esterification equilibrium and improving the yield.